العنف الموّجه ضد المرأة وعلاقته ببعض المتغيّرات الاجتماعية "دراسة ميدانية في مدينة اللاذقية" - حليوة, ليلى (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يعدّ العنف ضد المرأة ظاهرة اجتماعية تعاني منها الكثير من المجتمعات, وتعدّ هذه الظاهرة نتاجاً لما اعترى وظيفة التنشئة الاجتماعية في النظام الأسري من تغيّرات نشأت كظواهر سلبية للمدنيّة الحديثة. يتناول البحث الحالي العنف الموّجه ضد المرأة بأشكاله (اللفظي، والنفسي، والجسدي), وعلاقته بمجموعة من المتغيّرات الاجتماعية، كالحالة الاجتماعية, وحالة العمل, والمؤهل العلمي, والوضع الاقتصادي للأسرة, بالإضافة إلى أثر العادات والتقاليد, ولتحقيق أهداف البحث تمّ بناء استبانة وتوزيعها على عيّنة من النساء في مدينة اللاذقية, وبعد الدراسة والتحليل تمّ التوصل إلى النتائج الآتية: - إن أكثر أنواع العنف التي تتعرض لها المرأة هو من نوع العنف اللفظي والنفسي, وهي نادراً ما تتعرض للعنف الجسدي. - وجود فروق ذات دلالة إحصائية بين إجابات أفراد العيّنة في أشكال العنف تبعاً لمتغيّرات حالة العمل, والحالة الاجتماعية، والمؤهل العلمي، والوضع الاقتصادي للأسرة, وتأثير العادات والتقاليد. Violence against women is a social phenomenon experienced by many communities, which is a product of what plagued the function of socialization in the family system changes resulted from negative phenomena of modern civilization. This paper addresses violence against women (verbal, psychological and physical), and its relationship to a range of social variables such as the social and work status, educational qualification, and the economic status of the family, in addition to the impact of traditions. To achieve the research objectives, a questionnaire was made and administered on a sample of women in Lattakia city, and after the study and analysis we reached the following results: -The most common types of violence against women is a kind of verbal and psychological violence, but they are rarely subjected to physical violence. -The presence of statistically significant differences between the answers of respondents in the forms of violence depending on the state variables of work, marital status, educational qualification and the economic stutus of the family, and the impact of customs and traditions.